Economic Evaluation of Extraction High Purity Nanosilica from Rice Husk Ash in Industrial Scale for Adsorbent Polutant - Baariq Fauzaan Paryawan; Asep Bayu Dani Nandiyanto (Jurnal Teknik Industri, Sistem Informasi dan Teknik Informatika, 2023)
Material for adsorbent polutant is really needed these days and the material need to eco-friendly which lead to agricultural waste like biomass. With economic evaluation presented a preliminary economic evaluation of the larger scale production of high purity nanosilica from rice husk ash for adsorbent that need produce by large industries. Specificaly, the study was done by making variable in the cost of raw material, which ompared to several economic parameters such as GPM, PBP, and CNPV. The result after calculation of several parameter that the project was profitable by increasing raw material cost below 100% from the estimated raw material cost, informing the fact for the prospective fabrication for fulfilling the demand of nanomaterial like nanosilica with high purity that will use for reduce polutant all over the world.